Educational Strategies for Fortified Goat Milk Development Supported by Digital Financial Ecosystems - Hutahuruk, Marice Br; Junaedi, Achmad Tavip; Renaldo, Nicholas; Prayetno, Muhammad Pringgo; Prihastomo, Arih Dwi; Andi, Andi; Putri, Novita Yulia; Fransisca, Luciana; Faruq, Umar; Musa, Sulaiman (First Ciera Publisher, 2026)
The development of fortified goat milk offers a promising approach to addressing nutritional deficiencies while creating value-added opportunities in the dairy sector, particularly in rural and peri-urban communities. Despite its potential, many fortified goats milk initiatives remain small-scale due to limited entrepreneurial capacity, weak market integration, and low adoption of digital financial systems. This study aims to examine educational strategies that integrate fortified goat milk development with digital financial ecosystems to enhance enterprise sustainability and scalability. Using a mixed-methods approach, the study combines qualitative interviews and focus group discussions with quantitative survey analysis involving educators, students, dairy producers, and digital finance practitioners. The findings reveal that conventional education emphasizes technical production skills while neglecting financial literacy and digital finance competencies. Integrated educational strategies significantly improve digital banking adoption, financial management practices, and access to microfinancing, which in turn mediate improvements in business performance. The study contributes a novel interdisciplinary framework that links nutrition innovation education with digital finance literacy, offering practical insights for educators, policymakers, and development agencies seeking to strengthen fortified dairy value chains and promote inclusive, digitally enabled agro-entrepreneurship.